Risk factors and new diagnostic index for deep venous thrombosis of lower extremities in elderly patients with traumatic femoral neck fracture - Chen, Wenhao; Su, Zhiming; Liu, Quan; Bai, Xinxin; Huang, Jiyue; Weng, Shaohuang; Chen, Min (Frontiers in Surgery, 2023)
Abstract Purpose To determine the incidence and risk factors of deep vein thrombosis (DVT) of lower extremities at admission in elderly Chinese patients with femoral neck fracture, and to establish and evaluate a new DVT predictor based on these risk factors. Methods Patients who were hospitalized from January 2018 to December 2020 at three independent centers were reviewed. According to the results of lower extremities vascular ultrasound at admission, they were divided into DVT group and non-DVT group. Single and multivariate logistic regression analysis were applied to determine the risk factors leading to DVT, and then a prediction formula for DVT based on the risk factors was developed. The new predictive index of DVT is calculated by the formula. Receiver operating characteristic (ROC) curve analysis was used to determine the diagnostic value of different factors and the new predictive index. Results There were 203 elder patients were included in the final analysis after application of the exclusion criteria. 37 patients (18.2 %) were diagnosed as DVT by ultrasound, of which 33 thrombi (89.2 %) were in distal peripheral deep veins, 1 thrombus (2.7 %) was in proximal central deep vein and 3 thrombi (8.1 %) were in mixed deep veins. Multivariate logistic regression analysis showed that four factors including injured side, hemoglobin, fibrinogen, d-dimer were the independent risk factors for the incidence of DVT. On this basis, a new formula for DVT predictive factor was constructed: New predictive index=0.895 * injured side (right=1, left=0) + 0.899 * hemoglobin (<109.5 g/L =1, >109.5 g/L =0) + 1.19 * fibrinogen (>4.24g/L=1, <4.24g/L=0) + 1.221* d-dimer (>2.4mg/L=1, <2.4mg/L=0). The AUC value of this new developed index was 0.735. Conclusions This work showed that the prevalence of DVT in elderly patients with femoral neck fracture in China was high at admission. New DVT predictive value can be used as an effective diagnosis strategy for evaluation of thrombosis at admission.